Simulacra and Hyperreality in Lorcan Finnegan's Vivarium (2019) - Kusuma Wardani, Larasati Dinda (LITERA KULTURA : Journal of Literary and Cultural Studies, 2023)
The study examined Vivarium (2019), a film directed by Lorcan Finnegan, through the framework of Jean Baudrillard's simulacra and simulation notions. This dystopian sci-fi film cleverly incorporates societal commentary. The main goal was to reveal the representation of simulacra and hyperreality in the tale. The research uncovered three orders of simulacra, effectively transforming the Yonder estate into a virtual world. The first order shows startling similarities between the'real' world and the "Yonder" dwelling and its surroundings. According to Baudrillard, second-order simulacra occur when the simulated version dominates the original, which is 'unreal'. This is demonstrated when the characters adjust to ersatz food and a child's mysterious development. The third tier represents hyperreality, in which the simulated surpasses actual reality. The characters struggle with their knowledge of the simulation, as well as the offspring, whose physical appearance resembles that of humans but belong to a different species.